Optimal generator maintenance outage scheduling using integer programming - Nuqui, Reynaldo F.
An improved generator maintenance scheduling procedure for electric power systems is formulated. The model deviates from the traditional methods of solution but retains their computational efficiency. The maintenance scheduling problem is formulated as a 0 - 1 linear integer program. An enhanced version of the rigorous 0 - 1 implicit enumeration algorithm is coded into a computer software to determine the optimum outage schedules of generating units. The objective criterion is not limited to "levellizing reserve." The model is flexible in that it accepts a wide variety of useful criteria such as; (1) earliest possible schedule; (2) minimum changes from existing schedule and (3) least maintenance cost schedule. The model is tested using sample systems and the National Power Corporation's (NAPOCOR) Luzon Grid generating system. Using various classes of objective criteria, results are compared with other accepted methods. Experiences with the program indicates that the model is comparable (in terms of computing time) and superior (in terms of quality of optimal solution(s)) than the heuristic methods.